2019–2020 Florida Citrus Production Guide: Planting New Citrus Groves in Florida in the Era of Citrus Greening - Ariel Singerman; Marina Burani-Arouca; Stephen H. Futch (EDIS)
This 7 page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. In this article, we summarize the results of an analysis to examine the profitability of three tree densities under different production and market conditions. We found that establishing a new grove with a tree density similar to that of the state’s average is not profitable under current market conditions. In addition, such density only attains a modest return under potentially higher prices. Despite the higher level of investment required for planting higher-density groves, such investments are profitable under the assumptions and scenarios analyzed. Our results should prove useful to citrus growers looking to invest in alternatives that have the potential to improve their profitability. Written by Ariel Singerman, Marina Burani-Arouca, and Stephen H. Futch, and published by the Food and Resource Economics Department, March 2019.